Pemanfaatan Media Belajar Berbasis Artificial Intelegency dalam Pembelajaran Di MAN 2 Padangsidimpuan - Ahmad Sofyan Siregar (Yayasan Al-Ahliyah Al-Islamiyah Aek Badak, 2023)
This research explores the use of learning media based on Artificial Intelligence (AI) at MAN 2 Padangsidimpuan. By involving 36 teachers as respondents, this research analyzed the type of learning media used, the intensity of use of AI-based media, teachers' understanding of the technology, and the perceived benefits. The research results show that the majority of teachers still use conventional media, although 94.4% have used AI-based media. Canva and Quizizz are favorite media, but their intensity of use is limited. Teachers' understanding of AI varies, with around 16.6% having a very good understanding. Perceived benefits ranged from limited to very large, with approximately 44.4% experiencing moderate benefits. Even though the intensity of using AI-based media is quite high, there are still limitations in the type of media used, influenced by the teacher's level of understanding. In conclusion, the use of AI-based media at MAN 2 Padangsidimpuan is common, but further efforts are needed to increase understanding and optimize its potential in learning. Suggestions for future research include focusing on strategies for developing learning with AI-based media in the classroom